PROBLEMS OF POLYGAMY IN INDONESIA (Analysis of Law No. 1 of 1974 and KHI) - Zuhrah, Fatimah (Universitas Islam Negeri Alauddin Makassar, 2016)
Polygamy is permissible in Islam. However, an absolute requirement of polygamy applies for a husband. It is allowed only if the husband could deal justly with his wives. If he is unable to act justly, then he is obliged to have only one wife.The provisions on polygamy in Indonesia have been regulated by Law No. 1 Year 1974 on marriage, and as a form of positive response to regulate a man who wants to marry more than one woman. Likewise, Compilation of Islamic Law (Kompilasi Hukum Islam-KHI) also regulates the polygamy’s terms and conditions for Muslims.Ideally, the two regulations - Law No. 1/1974 and KHI– aim to provide terms and conditions of a man who wants to have next marriage. The provision is aimed to reduce men’s (husbands) arbitrariness on women (wives). Also, it helps in the creation of happy, prosperous, and peaceful family.